German exports and economic development - Reinhold Sohns (Intereconomics, 1976)
The influence of the export trade on the economic development since 1974 shows how greatly economic activities in the Federal Republic of Germany depend upon the situation abroad. In this context the author analyses the regional distribution and the goods structure of German exports and discusses their medium-term prospects.
Keywords: 330; Foreign Trade